Diseases caused by intestinal microorganisms - Єрьоміна, Алла Кузьмівна; Камишний, Олександр Михайлович; Кірсанова, Олена Валентинівна; Сухомлінова, Ірина Євгенівна (Запорізький державний медичний університет, 2016)
The independent practical work of students is an important part of the syllabus in the course of microbiology, immunology. It helps students to study this fundamental subject. The systematic independent work enables to reach the final goal in the students’ education. It is also important while preparing the students for their future clinic work with patients. These theoretical material, questions and tests help students to get ready for examination.
Захворювання, спричинені кишковими мікроорганізмами
Keywords: микробиология; мікробіологія